A Pre-clinical Animal Model of Trypanosoma brucei Infection Demonstrating Cardiac Dysfunction. - Charlotte S McCarroll; Charlotte L Rossor; Linda R Morrison; Liam J Morrison; Christopher M Loughrey (Public Library of Science (PLoS), 2015)
African trypanosomiasis (AT), caused by Trypanosoma brucei species, results in both neurological and cardiac dysfunction and can be fatal if untreated. Research on the pathogenesis and treatment of the disease has centred to date on the characteristic neurological symptoms, whereas cardiac dysfunction (e.g. ventricular arrhythmias) in AT remains largely unstudied. Animal models of AT demonstrating cardiac dysfunction similar to that described in field cases of AT are critically required to transform our understanding of AT-induced cardiac pathophysiology and identify future treatment strategies. We have previously shown that T. brucei can interact with heart muscle cells (cardiomyocytes) to induce ventricular arrhythmias in ex vivo adult rat hearts. However, it is unknown whether the arrhythmias observed ex vivo are also present during in vivo infection in experimental animal models. Here we show for the first time the characterisation of ventricular arrhythmias in vivo in two animal models of AT infection using electrocardiographic (ECG) monitoring. The first model utilised a commonly used monomorphic laboratory strain, Trypanosoma brucei brucei Lister 427, whilst the second model used a pleomorphic laboratory strain, T. b. brucei TREU 927, which demonstrates a similar chronic infection profile to clinical cases. The frequency of ventricular arrhythmias and heart rate (HR) was significantly increased at the endpoint of infection in the TREU 927 infection model, but not in the Lister 427 infection model. At the end of infection, hearts from both models were isolated and Langendorff perfused ex vivo with increasing concentrations of the β-adrenergic agonist isoproterenol (ISO). Interestingly, the increased frequency of arrhythmias observed in vivo in the TREU 927 infection model was lost upon isolation of the heart ex vivo, but re-emerged with the addition of ISO. Our results demonstrate that TREU 927 infection modifies the substrate of the myocardium in such a way as to increase the propensity for ventricular arrhythmias in response to a circulating factor in vivo or β-adrenergic stimulation ex vivo. The TREU 927 infection model provides a new opportunity to accelerate our understanding of AT-related cardiac pathophysiology and importantly has the required sensitivity to monitor adverse cardiac-related electrical dysfunction when testing new therapeutic treatments for AT.